Comparison of the Personality Profiles of Inmate Anonymous and Non-Anonymous Male Addicts - Nasrolah Erfani; Mohammad Poursina (Drug Control Headquarters, Research and Education Office, 2013)
Aim: This study compared the personality profiles of inmate anonymous and non-anonymous male addicts. Method: The participants of study were anonymous and non-anonymous male addicts of the prisons of the Hamadan province in 1391. The population was 3130 addicts, including 627 anonymous and 2503 non-anonymous addicts. The 310 addicts were selected by stratified random sampling the sample size was determined by Cochran formula.The short-form NEO Five Factor personality questionnaire administered among selected sample. Data analyzed by descriptive statistic as frequency and percentage, also, inferential statistic as multivariate analysis of variance was run. Results: The results showed that personality profiles of anonymous and non-anonymous addicts were significantly different. That is, mean score of neuroticism in anonymous addicts was less than non anonymous. Also, mean score of extraversion was higher in anonymous addicts. Conclusion: It can be concluded that the anonymous male addicts are differ with non-anonymous male addicts in personality traits.